Hotspots and trends in multiple myeloma bone diseases: A bibliometric visualization analysis - Hou, Zhaomeng; Jiang, Ping; Su, Shaoting; Zhou, Honghai (Frontiers in Pharmacology, 2022)
Objective: This study aims to explore the research hotspots and trends of multiple myeloma bone disease in the past 20 years by bibliometric visualization analysis. Methods: With the Web of Science core collection database as the data source, the relevant publications of multiple myeloma bone disease from 2002 to 2021 are retrieved. These data are analyzed using software CiteSpace 5.8.R3 and Scimago Graphica 1.0.24, together with the Online Analysis Platform of Literature Metrology. Results: A total of 6,168 published research papers, including 4668 articles and 1500 review papers, are included in this study. Generally speaking, annual publications and citations are on the rise, especially in recent two years. The majority of these papers are published in the United States, with Mayo Clinic being the greatest contributor. The most productive journal and author are Blood and Terpos E, respectively, while the most frequently co-cited reference, author and journal are Rajkumar SV, 2014, Lancet Oncol, Kyle RA and Blood, respectively. The major research subject categories are oncology and hematology. The “disease diagnosis”, “prognosis evaluation”, “pathogenesis”, “imaging technology” and “targeted therapy” are recent research frontiers. The burst keywords “transplantation”, “progression”, “activation”, “lenalidomide”, “flow cytometry”, “drug resistance”, “management” and “mesenchymal stem cell” reflect the latest research hotspots. Conclusion: This study reveals the research hotspots and trends of multiple myeloma bone disease through bibliometric visualization analysis, and provides a valuable reference for further research.